2018
DOI: 10.1111/een.12710
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal diversity in hyperparasitoid communities of Cotesia glomerata on garlic mustard, Alliaria petiolata

Abstract: 1. Interactions between two trophic levels can be very intimate, often making species dependent on each other, something that increases with specialisation. Some specialised multivoltine herbivores may depend on multiple plant species for their survival over the course of a growing season, especially if their food plants are short-lived and grow at different times. Later generations may exploit different plant species from those exploited by previous generations.2. Multivoltine parasitoids as well as their nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…By contrast, G. agilis is wingless and can cover a smaller area per unit of time compared with A. nens. Wingless Gelis species appear to prefer searching for hosts on or close to the ground instead of in the canopy of forbs (Harvey et al, 2014;Heinen & Harvey, 2019). Honeydew excreted by aphids not only accumulates on leaf surfaces of the food plant, but also falls to the ground (Moller & Tilley, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, G. agilis is wingless and can cover a smaller area per unit of time compared with A. nens. Wingless Gelis species appear to prefer searching for hosts on or close to the ground instead of in the canopy of forbs (Harvey et al, 2014;Heinen & Harvey, 2019). Honeydew excreted by aphids not only accumulates on leaf surfaces of the food plant, but also falls to the ground (Moller & Tilley, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Pieris spp. and C. glomerata prefer open landscapes with low tree cover where wild Brassicaceae cover is often higher (Heinen and Harvey 2019). Brassicaceae cover was highest in arable land, in particular cabbage fields, which suggests that (organic) arable land can support P. brassicae and P. rapae populations.…”
Section: Discussionmentioning
confidence: 96%
“…Brassicaceae cover in forests was rather low in our study area and consisted mostly of the species Allaria petiolata. While the main hosts of C. glomerata, P. brassicae and P. rapae, can oviposit on and feed from this plant species (Heinen et al 2016), it may not be their preferred host plant in natural conditions because of their occurrence in shaded habitats (Heinen and Harvey 2019). In contrast, Pieris spp.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on C. glomerata cocoons attached to leaves at the bottom of the plant or in the canopy, it was shown that wingless species such as Gelis proximus were predominant in the vegetation close to the ground whereas winged species such as Acrolyta nens were more abundant in the canopy. This demonstrates that community composition of hyperparasitoids can greatly vary even at small spatial scales . Temporal changes in hyperparasitoid communities were recorded in a monthly survey of aphid hyperparasitoids in organic sweet pepper greenhouses, where Dendrocerus aphidum was more abundant before summer and Asaphes vulgaris became more abundant in late summer (Table S1).…”
Section: Impact Of Hyperparasitoids On Biological Controlmentioning
confidence: 86%